Non-disjunction of chromosome 21, alphoid DNA variation, and sociogenetic features of Down syndrome - Vorsanova, S.G.; Iourov, I.Y.; Beresheva, A.K.; Demidova, I.A.; Monakhov, V.V.; Kravets, V.S.; Bartseva, O.B.; Goyko, E.A.; Soloviev, I.V.; Yurov, Y.B. (Цитология и генетика, 2005)
The analysis of non-disjunction of chromosome 21 and alphoid DNA variation by using cytogenetic and molecular cytogenetic techniques (quantitative fluorescence in situ hybridization) in 74 nuclear families was performed. The establishment of possible correlation between alphoid DNA variation, parental age, environmental effects, and non-disjunction of chromosome 21 was made. The efficiency of techniques applied was found to be 92 % (68 from 74 cases). Maternal non-disjunction was found in 58 cases (86 %) and paternal non-disjunction — in 7 cases (10 %). Post-zygotic mitotic non-disjunction was determined in 2 cases (3 %) and one case was associated with Robertsonian translocation 46,XX,der(21;21)(q10;q10),+21. Maternal meiosis I errors were found in 43 cases (64 %) and maternal meiosis II errors — in 15 cases (22 %). Paternal meiosis I errors occurred in 2 cases (3 %) and paternal meiosis I errors — in 5 cases (7 %). The lack of the correlation between alphoid DNA variation and non-disjunction of chromosome 21 was established. Sociogenetic analysis revealed the association of intensive drug therapy of infectious diseases during the periconceptual period and maternal meiotic non-disjunction of chromosome 21. The correlation between non-disjunction of chromosome 21 and increased parental age as well as exposure to irradiation, alcohol, tobacco, mutagenic substances was not found. The possible relevance of data obtained to the subsequent studies of chromosome 21 non-disjunction is discussed.